Peranan Badan Usaha Milik Desa (BUMDes) dalam Meningkatkan Pendapatan Masyarakat dan Pembangunan Desa Tinjauan Ekonomi Islam : Studi Kasus Kec. Kualuh Hilir, Kab. Labura - Muhammad Nur Tondi; Waizul Qarni; Nurul Jannah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
BUMDes (Village-Owned Enterprises) plays a strategic role in promoting community income and sustainable village development. This study aims to analyze the role of BUMDes in increasing community income and village development in Kualuh Hilir District, North Labuhanbatu Regency (Labura), from an Islamic business ethics perspective. The method used is descriptive qualitative with data collection through in-depth interviews, observation, and documentation of BUMDes administrators, village governments, and beneficiary communities. The results show that BUMDes in Kualuh Hilir District has contributed to increasing Village Original Income (PADes), providing employment, and empowering the local economy, although it still faces challenges in governance, human resource capacity, and financial transparency. From an Islamic business ethics perspective, BUMDes management needs to be based on ethical principles such as justice (adl), common welfare (maslahah), mutual assistance (ta'awun), trustworthiness (amanah), and the prohibition of riba, so that the benefits can be felt by all levels of society equitably.